Left atrial remodeling, early repolarization pattern, and inflammatory cytokines in professional soccer players - Stumpf, C.; Simon, M.; Wilhelm, M.; Zimmermann, S.; Rost, C.; Achenbach, S.; Brem, M. H. (Journal of Cardiology, 2016)
Objectives